2020
DOI: 10.1108/qmr-12-2017-0187
|View full text |Cite
|
Sign up to set email alerts
|

Service brand rehab: diagnosing trust repair mechanisms

Abstract: Purpose This paper aims to understand consumers’ response to the trust repair mechanisms adopted by corporate brands in a service sector context following prominent trust damaging organizational transgressions. Design/methodology/approach Adopting a qualitative approach, six focus group discussions are used to investigate three high-profile consumer trust erosion cases within the service sector. Findings Consumer trust varies by context. Despite the severity of trust damage, corporate brands can recover tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 41 publications
(138 reference statements)
1
11
0
Order By: Relevance
“…Finally, this study has demonstrated the applicability of Bachmann's trust repair framework. As this framework was developed in an organizational studies context, its applicability to other contexts had been questioned (Bozic, 2017) and only one study had established its use in a marketing context (see Bolat et al, 2020). The findings from this study establish the use of this integrative framework in a new context, political trust, and highlights how the use of the 6 mechanisms can help to identify patterns in the process of trust repair, i.e.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Finally, this study has demonstrated the applicability of Bachmann's trust repair framework. As this framework was developed in an organizational studies context, its applicability to other contexts had been questioned (Bozic, 2017) and only one study had established its use in a marketing context (see Bolat et al, 2020). The findings from this study establish the use of this integrative framework in a new context, political trust, and highlights how the use of the 6 mechanisms can help to identify patterns in the process of trust repair, i.e.…”
Section: Discussionmentioning
confidence: 86%
“…In summary, research within the political trust domain has to-date identified a limited range of trust repair responses. Bachman et al (2015) provide a comprehensive framework, and although the transferability of this framework to a non-organizational studies context has been questioned (Bozic, 2017) recent empirical research has demonstrated it applicability (see Bolat et al, 2020). Bachmann et al (2015) provide the most comprehensive framework for trust repair integrating six mechanisms or responses.…”
Section: Trust Repairmentioning
confidence: 99%
See 3 more Smart Citations